Utility Functions for Equity and Public Risk - Keeney, Ralph L. (Management Science, 1980)
With many large-scale projects, such as power plants, some members of the public will necessarily incur a risk. Public fatalities may result from either normal operations (e.g., via pollution) or accidents. Often in such cases, a small group of the public incur the risks, whereas a different group of the public receives the benefits from the project. In these circumstances, a major issue concerns the equity or fairness afforded members of the public. This paper develops the concept of an equitable distribution of risk to address this issue. Utility functions are found which are consistent with various basic value attitudes involving risk equity.